CQCQ
Member level 3
Hi! I have some problem with S=S0*cos(ωf-kz+φ)
1.why "wave" can express as S=S0*cos(ωf-kz+φ)?
2.If I can take"sin"instead of cos as S=S0*sin(ωf-kz+φ)?
3.What is "ωf" means in the expression?
4.Whas is "-kz" and why not "+kz"?
5.what is "φ" and why not "-φ"?
-CQCQ
Thanks!
1.why "wave" can express as S=S0*cos(ωf-kz+φ)?
2.If I can take"sin"instead of cos as S=S0*sin(ωf-kz+φ)?
3.What is "ωf" means in the expression?
4.Whas is "-kz" and why not "+kz"?
5.what is "φ" and why not "-φ"?
-CQCQ
Thanks!